2005
DOI: 10.1073/pnas.0507728102
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule Förster resonance energy transfer study of protein dynamics under denaturing conditions

Abstract: Proteins are highly complex systems, exhibiting a substantial degree of structural variability in their folded state. In the presence of denaturants, the heterogeneity is greatly enhanced, and fluctuations among vast numbers of folded and unfolded conformations occur via many different pathways. Here, we have studied the structure and dynamics of the small enzyme ribonuclease HI (RNase H) in the presence of the chemical denaturant guanidinium chloride (GdmCl) using single-molecule fluorescence microscopy, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
172
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(188 citation statements)
references
References 46 publications
14
172
0
2
Order By: Relevance
“…At more than 5 M GdmCl, the native peak was no longer obvious because of the low proportion of native state. The denatured peak shifted significantly to lower FRET efficiency with the increase of GdmCl concentration (from FRET efficiency of 0.65 at 3 M GdmCl to 0.49 at 6 M GdmCl), which was likely caused by the expansion of the denatured state at higher denaturant concentration, as observed in previous studies (6,21). There was a much less, but still observable, shift for the native peak between 0 and 2 M GdmCl (from 0.89 to 0.82 in FRET efficiency).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…At more than 5 M GdmCl, the native peak was no longer obvious because of the low proportion of native state. The denatured peak shifted significantly to lower FRET efficiency with the increase of GdmCl concentration (from FRET efficiency of 0.65 at 3 M GdmCl to 0.49 at 6 M GdmCl), which was likely caused by the expansion of the denatured state at higher denaturant concentration, as observed in previous studies (6,21). There was a much less, but still observable, shift for the native peak between 0 and 2 M GdmCl (from 0.89 to 0.82 in FRET efficiency).…”
Section: Resultssupporting
confidence: 61%
“…Direct observation of distinct states of BBL in the transition region at equilibrium would provide compelling evidence for barrier limited folding (6,13). The current method of choice is single-molecule fluorescence resonance energy transfer (SM-FRET) experiments, which has been widely applied in the studies of protein folding, structure, and function, and is especially useful in detection of heterogeneity of populations (14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18] In addition, several single-molecule fluorescence resonance energy transfer studies 26,29,32 have shown that conformational transitions within an unfolded protein ensemble could occur on a range of timescales, signifying the underlying hierarchical nature of the unfolded potential well. While these previous studies provided valuable insights into the statistical properties of unfolded polypeptide chains, they mainly focused on relatively small and mostly single-domain proteins.…”
mentioning
confidence: 99%
“…16 Similarly, the specific dye shape and mutual orientation are crucial and are not fully captured by simple accessible volume calculations. 17 Molecular dynamics simulations also allow testing assumptions such as approximating the mutual dye-dye orientation factor κ 2 with 2/3, which is questioned in several studies, 18,19 in particular, for low linker flexibilities. 20 Many simulation protocols have computationally prohibitive demands to reach sufficiently long simulation times for accurate calculations of experimentally accessible properties.…”
Section: Introductionmentioning
confidence: 99%